2003
DOI: 10.1213/01.ane.0000062524.90936.1f
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human TREK-1 Channels by Bupivacaine

Abstract: The interaction of bupivacaine with human TREK-1 channels was studied with the patch-clamp technique. Bupivacaine inhibited TREK-1 channels and depolarized the membrane potential of cells expressing TREK-1 channels in a concentration-dependent and reversible manner. Both effects may contribute to conductance block caused by bupivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…We also found that 10 μmol/L AA increased TREK-1 current by 60.0%±3.6% (n=6) ( Figure 1Cc). These results are consistent with previous reports regarding the properties of TREK-1 channels [22] .…”
Section: Electrophysiological Properties Of Trek-1 Channelssupporting
confidence: 94%
“…We also found that 10 μmol/L AA increased TREK-1 current by 60.0%±3.6% (n=6) ( Figure 1Cc). These results are consistent with previous reports regarding the properties of TREK-1 channels [22] .…”
Section: Electrophysiological Properties Of Trek-1 Channelssupporting
confidence: 94%
“…Application of a number of anaesthetic agents have been demonstrated to either activate or inhibit K 2P channels. The local anaesthetic bupivicaine has been reported to inhibit a number of tandem pore channels [20] including TASK-2 [19] and TREK-1 [34]. Application of 1 mM bupivicaine to the apical aspect of Calu-3 monolayers inhibited the basal I sc by 11.4±1.7 lA cm À2 or 39.6±9.0% (n = 13; Fig.…”
Section: Evidence For Functional K 2 P Channels In Calu-3 Cellsmentioning
confidence: 92%
“…We firstly demonstrated whether three K 2 p channels (TREK-1, TREK-2, and TRAAK) were expressed in neural stem cells (NSCs) derived from the hippocampus of fetal Sprague-Dawley rats. The proliferation, differentiation, and apoptosis of embryonic NSCs were then evaluated under two opposing regime where TREK-1 had been overexpressed by transfection with an hTREK-1 gene or suppressed by bupivacaine and curcumin, two strong TREK-1 channel inhibitors (Enyeart et al 2008;Punke et al 2003), respectively. Secondly, we investigated the influence of dexamethasone (DEX), a glucocorticoid hormone receptor agonist, on the proliferation and TREK-1 expression of embryonic NSCs.…”
Section: Introductionmentioning
confidence: 99%